El acceso a los recursos educativos por los docentes de educación secundaria: un estudio exploratorio - Tafur Puente, Rosa (2010)
Access to educational resources by teachers contributes to improve the quality ofteaching and learning at school. In order to inquiry to what extent teachers accessto these resources an exploratory study took place in eight public schools of Lima.School libraries and innovation classrooms were observed, a survey was applied toteachers; there were also focus groups with them and interviews to schools’ principals.Results reveal the scarce availability of resources that teachers have at schools,the precariousness of school libraries in collections, personnel and services, thepoor development of innovation classrooms, as well as the gap between the officialdiscourse and the practice in order to reach educational achievements